Effects of different methods of slaughtering on protein expression in chicken meat - Zaman, Rahela; Mohd Nasir, Mohd Hamzah; Abdulrazaq, Nafiu Bidemi; Mohd. Salleh, Hamzah; Rahman, Mohammad Tariqur (IIUM Press, 2012)

(untitled)
We have investigated variation of total protein profile in chicken skeletal muscle expected to be influenced due to variation in method of slaughtering. Two types of samples, depending on the method of slaughtering using sharp knife, were examined: (i) CT- neck was cut off completely and body was tied until the animal died and (ii) PRneck was cut off partially leaving the spinal cord intact and body was released immediately after slaughtering. Proteins expressed in higher amount were mostly found to be distributed in the range of Mw 45-66 kDa as resolved using SDS-PAGE. While resolved in 2D-PAGE, differences in protein expression were observed between samples. Protein spotted on the gel near pH 5.0 and Mw 116 kDa was found in the skeletal muscle from CT while it was absent the samples from PR.